Segmental morphometrics of the southern yellow-cheeked crested gibbon (Nomascus gabriellae): the case study of four individuals in zoo - François Druelle; Mélanie Berthet (Revue de Primatologie)
Gibbon species are highly specialized for brachiation. Nevertheless, as with all primates, they are capable of various posturo-locomotor modes as part of a larger overall positional repertoire. In this context, the study of their locomotor apparatus is very relevant to better understand their evolution toward such specialization for brachiation on the one hand, and the degree to which their body may reflect compromises on the other hand. Indeed, gibbons also frequently use a variety of other non-brachiating locomotor modes – including bipedalism, leaping and climbing – that are crucial during arboreal travel. Here, we present a dataset of external morphometrics and estimates of segmental inertial properties for Nomascus gabriellae – the first such data collected for this species. Measurements were taken on four captive animals during a routine veterinary exam coinciding with maintenance to their enclosure within the zoo. We compared our dataset to the only available and comparable sample of gibbon morphometrics (three Hylobates lar and one Symphalangus syndactylus). Our results show that these species appear very similar in terms of body shape. Nevertheless, H. lar and N. gabriellae are more similar to each other than either is to S. syndactylus, which is also twice as large. Slight differences in segmental mass and limb center of mass position are highlighted and may point to differences in the locomotor profiles of these hylobatids. These relationships are discussed in the light of the biomechanical theory.